International Research Collaboration During the Pandemic: Team Formation, Challenges, Strategies and Achievements of the African Translational Research Group - Envuladu, E.A.; Miner, C.A.; Oloruntoba, Richard; Osuagwu, U.L.; Mashige, K.P.; Amiebenomo, O.M.; Abu, E.K.; Timothy, C.G.; Ovenseri-Ogbomo, G.; Ekpenyong, B.N.; Langsi, R.; Goson, P.C.; et al. (SAGE PUBLICATIONS INC, 2022)
This paper discusses multidisciplinary international research collaboration team formation during the COVID-19 pandemic, challenges faced, strategies adopted, achievements and dynamics in the implementation of research on Coronavirus disease-2019 (COVID-19), by the African Translational Research Group (ATReG). The paper also discusses the lessons learnt and future opportunities for global collaborative research. In-depth virtual interviews were conducted with consenting members of ATReG. Questions were designed to provide rich, deep, and insightful opinions, lived experiences and perspectives of ATReG group members on group formation, challenges, strategies and achievements. Interview data was transcribed and analysed thematically, and the results were presented with important quotations presented. The ATReG consisted of English (n = 13) and French (n = 1) speaking sub-Saharan African (SSA) researchers who specialise in public health, epidemiology, optometry, information technology, supply chain management, psychiatry, community health, general medical practice, nutrition and biostatistics. Most members of the group reported an informal but well-coordinated structure of the group. Formed during the pandemic, all group meetings were held online, and many members are yet to meet each other in person. The group collected data from Africans and published 10 peer reviewed journal articles on COVID-19 within two years. It presented in international conferences, engaged with the media and the public and was awarded a national competitive funding in Nigeria all of which which contributed to career progression and academic promotion of some members. There have been challenges in sustaining the research collaboration and maintaining productivity. Challenges include difficulties meeting deadlines and obtaining funding for research activities. However, these challenges have been addressed through a collaborative problem-solving approach. The study found the need for operational and methodological flexibility, centralised coordination, and established funding sources as being essential for long term sustainability and performance of the group. The ATReG’s objective of providing useful data on COVID-19 and generating useful knowledge about COVID-19 in SSA has been achieved. In such a multi-disciplinary international collaborative team relaiant on the online medium to operate, the experiences and challenges can be a model for learning for researchers intending to form international multidisciplinary collaborative groups. Nonetheless, there are still many important areas of research which ATReG will continue to pursue.